Assessing the Introduction of Genetically Modified Organisms (GMOs) into Ghana: The Perspectives of Agriculture Professionals in Northern Region - Badmus, Mutiu; Abubakar, Muhammed Charmawla; Zakari, Baasit Abdul (International Journal of Environment, Agriculture and Biotechnology, 2024)
The role of agriculture officers is essential and cannot be ignored when introducing technology such as Genetically Modified Organisms (GMOs). However, there is no known study presently that examines agriculture officers’ perspectives of GMOs emergence in Ghana. Our study assesses agriculture officers’ perceptions on the introduction of GMOs into Ghana and its impact on food and seed security as well as officer’s level of involvement in GMOs related activities and willingness to promote it. We further solicited their views on GMOs as a successful solution to tackle farming challenges and assessed what influenced their views. Our findings revealed that 53% of agriculture officers agreed that GMOs will have positive impact on food/ seed security/sovereignty. Also, 56% said they will champion GMOs, however, 67% said there is limited information on GMOs and 74% of the respondents indicated that they have never attended or participated in GMOs related activity. We highlighted officers’ divergent views around the introduction of GMOs as a successful solution to tackle farming challenges and the key influencers include: GMOs is unsafe for human consumption, gene escape into wild relatives, and possibility of creating insect resistant and limited capacity to genetically engineered crops locally. The study recommended that there is the need for pro and anti-GMO groups to involve officers in GMO activities for effective dissemination of information on GMO to farmers or citizens.